Barriers, borders and crossing in two postmodern novels: Caryl’s Phillips’s The Nature of Blood and Zadie Smith’s White Teeth - Acquarone, Cecilia (Epos : Revista de filología, 2008)
The present article is a study of the novels the Nature of Blood by Caryl Phillips and White Teeth by Zadie Smith as paradigmatic examples of postmodern writing as well as of two different responses that the movement has elicited in our times. While The Nature of Blood deals tragically with the postmodern condition, White Teeth laughs at the contradictions and celebrates the achievements of postmodernism.